On Ectopia Cordis With Omphalocele With Dolichocephaly With Kyphosis - Jaiswal, Parul; Suryarao, Prashant (Journal of Neonatal Surgery, 2025)
Ectopia cordis is a rare and severe congenital anomaly characterized by the abnormal positioning of the heart outside the thoracic cavity. It is frequently associated with midline defects, such as omphalocele and vertebral anomalies, leading to high perinatal mortality. This case report describes a 27-year-old gravida 2, abortion 1 patient who underwent a routine prenatal ultrasound at 17 weeks of gestation, revealing a complex presentation of ectopia cordis, omphalocele, dolichocephaly, kyphosis, and spina bifida with meningocele. Additional findings included severe oligohydramnios (AFI: 1-2 cm), fetal bradycardia (heart rate: 80 bpm), and nuchal fold thickness of 2.9 mm. Given the poor prognosis, the parents opted for pregnancy termination at 19 weeks. Postnatal examination confirmed the presence of an anterior thoracoabdominal wall defect with an ectopic contractile heart, omphalocele containing the liver, spleen, small intestines, and colon, and a dysmorphic facial profile indicative of dolichocephaly. The umbilical cord was directly inserted into the herniated segment. Despite normal limb morphology, the thoracic spine showed kyphosis. The fetus weighed 119 grams. This case highlights the critical role of prenatal ultrasonography in early diagnosis and parental counselling. Ectopia cordis, especially when associated with multiple congenital anomalies, presents significant challenges in management, requiring a multidisciplinary approach for surgical intervention in select cases. Understanding the genetic and environmental factors contributing to such complex anomalies is essential for improving prenatal screening and postnatal outcomes. Further research and case studies may provide deeper insights into the pathogenesis and potential treatment modalities for such rare congenital conditions.